2019
DOI: 10.53543/jeps.vol13iss4pp715-732
|View full text |Cite
|
Sign up to set email alerts
|

Students' Reluctance to Attend Office Hours: Reasons and Suggested Solutions

Abstract: This paper focuses on investigating students’ reasons for their reluctance to attend faculty members’ office hours. Study participants included 500 male and female students from the Colleges of Engineering (n = 248) and Arts and Social Sciences (CASS) (n = 252) at Sultan Qaboos University (SQU). The study followed a descriptive-analytical approach, and a questionnaire was utilized to collect people’s views. The results of the study indicate that the rates of SQU students’ attendance to office hours were low, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In the past, students typically contacted faculty around class times, [26] but students' schedules are not always conducive to faculty office hours, [2,21] thus creating missed opportunities for interaction. Faculty in this study reported being open to meeting the needs of students by showing a willingness to meet outside designated office hours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the past, students typically contacted faculty around class times, [26] but students' schedules are not always conducive to faculty office hours, [2,21] thus creating missed opportunities for interaction. Faculty in this study reported being open to meeting the needs of students by showing a willingness to meet outside designated office hours.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the ease and availability of technology, students still underutilize office hours, which is supported by current and historical research. [3,6,17,21,27,29] This may be why faculty will meet outside of office hours and strive to respond to student inquiries within a 24 to 48-hour timeframe. The consensus was that students expect a fast turnaround when reaching out to faculty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The completion of assignments during lab time also increases equity regarding access to support and student success, as students are able to seek instructor assistance during scheduled course time rather than during instructor drop-in (office) hours, when they may have a time conflict or apprehension of attending. 35 Each instructor creates six teams of four students. During the first week of the lab, students complete a "Who Are You" survey via the JMU LMS to provide the instructors with additional information to facilitate team formation and lab operation (e.g., allergies or disabilities).…”
Section: Inquirymentioning
confidence: 99%